Tests of a Deferred Tax Explanation of the Negative Association between the LIFO Reserve and Firm Value* - DHALIWAL, DAN S.; TREZEVANT, ROBERT H.; WILKINS, MICHAEL S. (Contemporary Accounting Research, 2000)
Abstract Guenther and Trombley (1994) and Jennings, Simko, and Thompson (1996) document a negative association between a firm's last‐in, first‐out (LIFO) reserve and the market value of its equity. In this paper, we test a deferred tax explanation of this negative association. Specifically, we argue that investors, conditional on adjusting inventory to as‐if first‐in, first‐out (FIFO), estimate a firm's future LIFO liquidation tax burden as its LIFO reserve multiplied by the appropriate corporate tax rate and include this tax‐adjusted LIFO reserve in the valuation of a LIFO firm's net assets. On the basis of this argument, the tax‐adjusted LIFO reserve is in effect an estimate of an off‐balance‐sheet deferred tax liability and, as a result, we predict a negative association between the tax‐adjusted LIFO reserve and market value of equity. We test our deferred tax explanation by estimating a valuation model in which a firm's market value of equity is expressed as a function of the firm's assets, liabilities, deferred tax liability, and tax‐adjusted LIFO reserve; the model is estimated separately in years preceding and following the reduction of tax rates mandated by the US Tax Reform Act of 1986. Test results provide strong support for the deferred tax explanation of the negative association between a firm's LIFO reserve and the market value of its equity.